Afatinib for the treatment of EGFR mutation-positive NSCLC: A review of clinical findings. (September 2020) - Harvey, R Donald; Adams, Val R; Beardslee, Tyler; Medina, Patrick
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors represent the standard of care in patients with EGFR mutation-positive ( EGFR m+) non-small cell lung cancer (NSCLC). The availability of several EGFR tyrosine kinase inhibitors approved for use in the first-line or later settings in NSCLC warrants an in-depth understanding of the pharmacological properties of, and clinical data supporting, these agents. The second-generation, irreversible ErbB-family blocker, afatinib, has been extensively studied in the context of EGFR m+ NSCLC. Results from the LUX-Lung 3 and 6 studies showed that afatinib was more active and better tolerated than chemotherapy in patients with tumors harboring EGFR mutations. Subanalysis of these trials, along with real-world data, indicates that afatinib is active in patients with certain uncommon EGFR mutations (S768I/G719X/L861Q) as well as common mutations (Del19/L858R), and in patients with active brain metastases. In LUX-Lung 7, a head-to-head phase IIb trial, afatinib improved progression-free survival and time-to-treatment failure versus the first-generation reversible EGFR tyrosine kinase inhibitor, gefitinib, albeit with a higher incidence of serious treatment-related adverse events. Nevertheless, afatinib is generally well tolerated, and adverse events are manageable through supportive care and a well-defined tolerability-guided dose adjustment scheme. In this review, we provide a detailed overview of the pharmacology, efficacy, and safety of afatinib, discuss treatment sequencing strategies following emergence of different resistance mechanisms, and shed light on the economic impact of afatinib. We also provide a comparison of afatinib with the available EGFR tyrosine kinase inhibitors and discuss its position within treatment strategies for patients with EGFR m+ NSCLC.